Monastic Libraries from Bessarabia – Collection Centers of Old Books Patrimony - CERETEU, Igor (Études Interdisciplinaires en Sciences humaines, 2020)
Abstract: The research of the monastic libraries contributes to a great extent to the identification of lesser known information about the bibliophile or secular church values and to the capitalization of novel manuscripts inscriptions, written by the owners or readers. According to the latest estimates in Bessarabia there are 27 monasteries and old hermitages, 37 missing and 38 monastic settlements are established in the last decades. The oldest of these (Capriana, Varzaresti, Hancu, Curchi) served as centers for spreading the written culture in eastern Moldavia through the copyist monks, living in these monastic settlements. During the Soviet era, only Japca was functioning, and our recent investigations have shown that most of the books in the library have burned after repeated fires during the second half of the 20th century. The library of the New Neamt Monastery was preserved in the funds of the National Archives of the Republic of Moldova, which require a multidimensional research. During its existence, however, several manuscripts and printed books have been alienated, some of which are currently in public libraries funds, private libraries, museums, churches and monasteries. Recent researches have convinced us that some monasteries have partially reconstituted their libraries and completed them with ancient Romanian and foreign books that they present themselves as true bibliophilic heritage research centers. We have also succeeded in specifying within the boundaries of the information in the notes or on the basis of the archive data the moment of founding the monastic libraries and watching the phenomenon of the circulation of the books, the branches and the itineraries on which these have moved in time and space.